Peran Kepala Keluarga Kristen (Ayah) dalam mendidik Anak Generasi Z dan Alpha - Yakub Hendrawan Perangin Angin; Tri Astuti Yeniretnowati (APOSTOLOS, 2021)
The role of fathers in educating children is still lacking. Children lack role models and expectations, flexible time and a lack of community. Because Dad makes a living from morning till night. The father's role for generation Z and A (Alpha) children is significant, considering that children exist in the digital era. The influence of information and technology and the values ??that are different and even contrary to the Bible's values have a considerable impact. The author uses descriptive qualitative methods. This research is intended to make fathers understand their strategic role in educating children in the digital generation, both for the children themselves, for families, churches and the world community. The father's primary calling is to model his attendance to Christ, which is his children's eternal legacy.